Helicobacter Pylori New Approaches of an Old Human Microorganism - Maria Roesler, Bruna (IntechOpen, 2019)
Helicobacter pylori is an universally distributed bacterium which affects more than half of the world population. H. pylori infection causes persistent inflammation with different clinical outcomes in humans, including chronic gastritis, peptic ulcer disease and gastric cancer. The infection has also been associated with several extradigestive disorders. In this book there is a comprehensive overview of contributors on H. pylori infection in diverse areas, including virulence factors of H. pylori and their importance for the clinical outcome of the diseases, discussions about the principal therapeutic regimens of bacterium eradication, also considering the antimicrobial resistance. H. pylori is clearly a very interesting bacteria and great studies and discussions about all its aspects are welcome to the medical and scientific communities.